How to Assess Drugs in the Treatment of Acute Bipolar Mania? - Bourin, Michel; Thibaut, Florence (Frontiers in Pharmacology, 2013)
Bipolar affective disorder is a serious mental disease associated with significant morbidity and mortality. Good-quality research available to guide treatment strategies remains insufficient, particularly with regard to manic or hypomanic episodes. A critical review of the various stages of mania might be helpful for pharmamaceutical companies and investigators as a prerequisite for the clinical evaluation of potential antimanic properties of medications. The main difficulty remains the comparison between antipsychotics and mood stabilizers such as lithium (with equal efficacy in the acute phase and the prevention of recurrent manic episodes) No consensus has been reached with regard to the treatment of bouts of acute mania in various parts of the world. Controlled clinical trials have, at last, provided irrefutable evidence of the activity of lithium, which has long been used alone, as well asthat of divalproate or its derivatives and, to a lesser extent, carbamazepine. The new antipsychotic agents have more recently established their efficacy, especially aripiprazole, asenapine, quetiapine; olanzapine, risperidone and ziprazidone. It is paradoxical to note that, in Europe, haloperidol is still the reference substance used in clinical trials despite the fact that it is not officially indicated in the treatment of mania. In the USA, lithium, divalproate or antipsychotics can be prescribed as first-line treatment. In Europe, lithium remains the first-line medication, whereas divalproate and atypical antipsychotic agents are used only as second-line therapy. Although both types of medication (antipsychotics, normothymic agents and/or anticonvulsants) have proved to be clinically effective in the management of mania by reducing the mania scores overall, the same does not apply, however, to all symptoms of mania. Factorial approaches to mania have all shown that since there are several clinical forms of mania, several lines of manic symptoms can be identified. Antipsy